2021
DOI: 10.1097/acm.0000000000004388
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Relationships and Gender Inequities in Academic Medicine: Findings From a Multi-Institutional Qualitative Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The data reported in this article are drawn from a parent study which utilized qualitative, semi-structured interviews to examine women's and men's understandings of multiple dimensions of gender inequities in academic medicine. 20 , 21 The study was informed by social constructionist or constructivist traditions, which consider the examination of participants’ understandings of their own experiences an important element of studying social phenomena. 22 , 23 We employ a social constructionist approach to gender, which holds that differences between women and men are a product of social interactions, rather than a reflection of innate, biological differences.…”
Section: Methodsmentioning
confidence: 99%
“…The data reported in this article are drawn from a parent study which utilized qualitative, semi-structured interviews to examine women's and men's understandings of multiple dimensions of gender inequities in academic medicine. 20 , 21 The study was informed by social constructionist or constructivist traditions, which consider the examination of participants’ understandings of their own experiences an important element of studying social phenomena. 22 , 23 We employ a social constructionist approach to gender, which holds that differences between women and men are a product of social interactions, rather than a reflection of innate, biological differences.…”
Section: Methodsmentioning
confidence: 99%
“…Initiatives aiming at how to strategically tackle gender equity among professionals, through networking and mentoring supported by societies and organisations, are in place [ 4 , 5 , 6 , 7 ], but not much has been done to relieve the struggle commonly associated with long operations. There is evidence that female surgeons experience more discomfort in their bodies and their hands than their male colleagues [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Successful individuals attribute career satisfaction and achievement to their mentorship. 5,9,10 Mentorship has been correlated with faculty retention, scholarly production, career satisfaction, better developed professional identities, and balance between professional and personal lives. 5,11 Mentoring is especially important for those who have been systematically disenfranchised.…”
mentioning
confidence: 99%
“…9,12 A recent scoping review focused on mentoring for women found that mentoring can both uncover inequalities and help mentees negotiate success but also revealed sexual harassment within mentoring relationships and continued difficulties reporting sexual harassment. 10 Sponsorship has been cited as especially key to opening doors for women and those URiM. 6,13,14 Challenges and failed mentor relationships were characterized by poor communication, lack of commitment by either mentee or mentor, lack of experience, personality differences, competition, conflicts of interest, and at worst, abuse of power by the mentor.…”
mentioning
confidence: 99%